Liposomal Bupivacaine in Implant-Based Breast Reconstruction. Issue 11 (November 2017) - Motakef, Saba; Wong, Wendy W.; Ingargiola, Michael J.; Nguyen, David; Galdyn, Izabela A.; Kim, Hahns Y.; Gupta, Subhas C.
Abstract : Purpose: This study evaluates the role of liposomal bupivacaine in implant-based breast reconstruction. Methods: A prospective, randomized, single-blind trial of liposomal bupivacaine in implant-based breast reconstruction was performed. Patients in the control arm were treated with 20 mL 0.25% bupivacaine with epinephrine 1:200, 000 to each breast pocket. Patients in the experimental arm were treated with 10 mL 1.3% liposomal bupivacaine delivered to each breast pocket. Pain scores were recorded over the course of patients' hospital stay. Consumption of pain medications, benzodiazepines, and anti-emetics was monitored. Length of stay and other direct cost data were collected. Results: Twenty-four patients were enrolled, with 12 women randomized to each arm. Average postoperative pain scores were 3.66 for patients in the control arm and 3.68 for patients in the experimental arm. Opioid consumption was 1.43 morphine equivalent dosing/h for patients in the control arm and 0.76 morphine equivalent dosing/h for patients in the experimental arm ( P = 0.017). Diazepam consumption was 0.348 mg/h for patients in the control arm and 0.176 mg/h for patients in the experimental arm ( P = 0.011). Average length of hospital stay was 46.7 hours for patients in the control arm and 29.8 hours for patients in the experimental arm ( P = 0.035). Average hospital charges were $18, 632 for patients in the control arm and $10, 828 for patients in the experimental arm ( P = 0.039). Conclusions: Liposomal bupivacaine reduces opioid and benzodiazepine consumption, length of stay, and hospital charges. These data support a role for liposomal bupivacaine in implant-based breast reconstruction.